Regulation of T Cell Differentiation and Function by EZH2 - Karantanos, Theodoros; Christofides, Anthos; Bardhan, Kankana; Li, Lequn; Boussiotis, Vassiliki A. (Frontiers in Immunology, 2016)
The enhancer of zeste homologue 2 (EZH2), one of the polycomb group (PcG) proteins, is the catalytic subunit of Polycomb-repressive complex 2 (PRC2) and induces the trimethylation of the histone H3 lysine 27 (H3K27me3) promoting epigenetic gene silencing. EZH2 contains a SET domain promoting the methyltransferase activity while the three other protein components of PRC2, namely EED, SUZ12 and RpAp46/48 induce compaction of the chromatin permitting EZH2 enzymatic activity. Numerous studies highlight the role of this evolutionary conserved protein as a master regulator of differentiation in humans involved in the repression of the homeotic (Hox) gene and the inactivation of X-chromosome. Through its effects in the epigenetic regulation of critical genes, EZH2 has been strongly linked to cell cycle progression, stem cell pluripotency and cancer biology. Most recently, EZH2 has been associated with hematopoietic stem cell proliferation and differentiation, thymopoiesis and lymphopoiesis. Several studies have evaluated the role of EZH2 in the regulation of T cell differentiation and plasticity as well as its implications in the development of autoimmune diseases and graft versus host disease (GvHD). In this review we will briefly summarize the current knowledge regarding the role of EZH2 in the regulation of T cell differentiation, effector function and homing in the tumor microenvironment and we will discuss possible therapeutic targeting of EZH2 in order to alter T cell immune functions.